Viral Hepatitis B and Its Implications for Public Health in DR Congo: A Systematic Review - Marcellin Mengouo Nimpa; Hermès Karemere; Christian Ngandu; Franck-Fortune Mboussou; M. Carolina Danovaro-Holliday; Dalau Nkamba; André Bita Fouda; Bienvenu Nguejio; Sifa Kakozi; Aimé Mwana-Wabene Cikomola; Jean-Crispin Mukendi; Dieudonné Mwamba; et al. (Viruses)
Background: The prevalence of hepatitis B virus infection remains high in the Democratic Republic of Congo (DRC), constituting a public health problem in view of the fatal complications it causes, notably cirrhosis and hepatocellular carcinoma. The aim of this study was to provide an overview of the situation of viral hepatitis B in the DRC and in particular its implications for public health. Methods: A systematic review was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) group guidelines. Google Scholar, PubMed, and ResearchGate were used as databases. The review essentially analyzed the viral hepatitis B (HBV) vaccination status of study subjects, diagnostic means, HBV genotypes in DR Congo, seroprevalence of HBV infection, subjects’ level of knowledge and perceptions of HBV, co-infection/comorbidity with HBV infection, factors associated with HBV infection and public health issues raised by HBV infection. Results: The vast majority of studies (69%) were carried out to determine the seroprevalence of HBV infection. The Determine rapid test was the most widely used test (10 studies), sometimes combined with ELISA (3 studies) and polymerase chain reaction (PCR) (1 study, for genotyping). Some of the public health issues raised by hepatitis B virus infection were identified in the course of the included studies, in relation to co-infection, comorbidity, associated factors, and individuals’ level of knowledge and perceptions of HBV. Certain factors were identified as being closely associated with HBV, notably healthcare professions (e.g., doctor, laboratory technician) and having several sexual partners. In terms of perception of HBV, the hepatitis B virus is recognized as dangerous, and the majority of people questioned in the various studies were aware that vaccination remains the most effective means of prevention. Conclusions: Hepatitis B is a highly contagious infectious disease present in the DRC, with a higher prevalence among healthcare professionals, sex workers, patients with certain diseases including HIV, and people with a history of blood transfusion. The surveillance system within the national blood transfusion program needs to be strengthened. Raising public awareness of the seriousness of viral hepatitis B, offering vaccination to at-risk populations, and systematically screening pregnant women and blood donors for HBV infection could help reduce the prevalence of viral hepatitis B.